KEMAMPUAN PENGGUNAAN TEKNOLOGI DAN MANAJEMEN RISET DALAM UPAYA MENGURANGI RISIKO BENCANA DI KABUPATEN BIMA - Suraya Suraya; Haeril Haeril (Jurnal Studi Ilmu Pemerintahan, 2022)
Local governments have problems in anticipating disasters, especially in the support of technology and communication system facilities. As a result, many casualties occurred repeatedly every time a natural disaster occurred. The urgency of the research is to describe the ability to use information technology and sustainable management research as an effort to reduce disaster risk in Bima Regency. The results of the study indicate that the operation of the Operations Control Center has provided improved performance in disaster management by the Regional Disaster Management Agency (BPBD) of Bima Regency. With the availability of a set of communication tools in the form of a mondopad monitor and radio communication for coordination in disaster management in the region to BNPB. The results of the research were then disseminated and disseminated, as well as disaster response simulations on campuses and schools in Bima Regency by involving international NGOs. In addition, the publication of research results can be used as a guide to reduce vulnerability by carrying out structural and non-structural mitigation. Basic efforts can be done by empowering the results of applied research from universities and research related to disaster management. One of them is through the study of the ratio of investment to each phase of disaster management.